Cultural Studies and the teaching of citizenship: analysing posters about the Aegean refugee drama - Papadima, Aspasia; Vamvakidou, Ifigenia; Tsioumis, Kostis (My University, 2017)
In this study three posters made by the graphic artist and Ass. Professor Aspasia Papadima (2016) are analysed in the context of modern and postmodern historical literacy. The trilogy of posters deals with the refugee drama that takes place in the Aegean as the result of the war in Syria and the human need for survival. The aim is to use the posters as an aid to teach our students the current concept of citizenship through the specific material for the immigrants in Aegean Sea, within the interdisciplinary field of cultural studies which draws from many different subject areas, including sociology, anthropology, political science, and history. Although it is sometimes misunderstood as being the study of popular culture, cultural studies are, in fact, the study of the ways in which culture is constructed and organized and the ways in which it evolves and changes over time. More specifically, our project focuses on the need of the artist to communicate through graphic pictorials, events that she considers to be of focal point in modern history of mankind. Analysis draws on Marshall’s classic social-democratic agenda, the aim of which was to reduce class inequality. The growing concern with cultural citizenship and identity reflects, to some extent, how issues that were once considered ‘social’ came increasingly to be thought of as ‘cultural’. Questions of identity and belonging have superseded questions of material entitlement in much social and cultural theory as well as in public policy and cultural politics (McGuigan 2004, 34). Following Raymond Williams’s (1984) distinction between cultural policy ‘proper’ (public patronage of the arts, media regulation, and construction of cultural identity), and cultural policy as display (national aggrandisement and economic reductionism) and the specifics of the Aegean refugee drama, lead us to consider cultural policy-making among the members of the European Union.
Keywords: Refugee; Aegean; Posters; Immigrants